Determinants Influencing Financial Performance of Public Hospitals: The Case of Vietnam (Asian Business Research, 2018)
The study is conducted to investigate the impact levels of determinants on financial performance of public hospitals in the Northwest of Vietnam in the discipline of management accounting. Data are collected from 43 public hospitals in the Northwest of Vietnam. Regression analysis is employed for determining the impact levels of factors on financial performance of public hospitals in Vietnam. The results show that the impact levels of determinants on financial performance decrease from the factors of efficiency of revenue and expenses, efficiency of staff working, mission role, quality standard, satisfaction of service quality, quality of treatment, service supply, strategic planning, financial management efficiency, mission achievement, activity strategy planning; customer’s expectations, ratio of doctor per patient. Based on the findings, some suggestions are given for improving financial performance of public hospitals in the Northwest in particular and public hospitals in Vietnam in general.